2018
DOI: 10.1007/s00222-018-0796-y
|View full text |Cite
|
Sign up to set email alerts
|

Counting and effective rigidity in algebra and geometry

Abstract: The purpose of this article is to produce effective versions of some rigidity results in algebra and geometry. On the geometric side, we focus on the spectrum of primitive geodesic lengths (resp., complex lengths) for arithmetic hyperbolic 2-manifolds (resp., 3-manifolds). By work of Reid, this spectrum determines the commensurability class of the 2-manifold (resp., 3-manifold). We establish effective versions of these rigidity results by ensuring that, for two incommensurable arithmetic manifolds of bounded v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…Additionally, they give an upper bound on the volume of their manifolds as a function of m. Inspired by [4], in this paper we consider the following question. This question was previously studied by the authors in [8]. Let π(V, S) denote the maximum cardinality of a collection of pairwise non-commensurable arithmetic hyperbolic 3-orbifolds derived from quaternion algebras, each of which has volume less than V and geodesic length spectrum containing S. In [8], it was shown that, if π(V, S) → ∞ as V → ∞, then there are integers 1 ≤ r, s ≤ |S| and constants c 1 , c 2 > 0 such that…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, they give an upper bound on the volume of their manifolds as a function of m. Inspired by [4], in this paper we consider the following question. This question was previously studied by the authors in [8]. Let π(V, S) denote the maximum cardinality of a collection of pairwise non-commensurable arithmetic hyperbolic 3-orbifolds derived from quaternion algebras, each of which has volume less than V and geodesic length spectrum containing S. In [8], it was shown that, if π(V, S) → ∞ as V → ∞, then there are integers 1 ≤ r, s ≤ |S| and constants c 1 , c 2 > 0 such that…”
Section: Introductionmentioning
confidence: 94%
“…For any subfield F ⊂ K, we have a homomorphism Res K/F : Br(F) → Br(K) given by Res K/F ([B]) = [B ⊗ F K]. For a pair of number fields K, K ′ , a natural isomorphism between Br(K), Br(K ′ ) is an isomorphism Φ Br : Br(K) → Br(K ′ ) such that for any F ⊂ K ∩ K ′ and any L with KK ′ ⊂ L, the diagram In [19] (see also [16]), it was shown that these fibers determine the algebra in certain situations. As in [20] however, there are situations when these fibers fail to determine the algebra.…”
Section: Introductionmentioning
confidence: 99%
“…Every totally geodesic surface is the area minimizing representative in its homotopy class, and we denote the set of all areas contributed by totally geodesic Our next theorem revisits a construction of pairs of incommensurable arithmetic hyperbolic 3manifolds with the same set of commensurability classes of surfaces up to an arbitrary threshold that appeared in [18,Section 7]. In particular we construct an infinite family of incommensurable arithmetic hyperbolic 3-manifolds whose geometric genus spectra start off with the same N terms and in which both volume and systole length are controlled.…”
Section: Introductionmentioning
confidence: 99%